2004
DOI: 10.1002/jbm.a.20129
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bioprosthetic heart valve tissue with long chain alcohol solution to lower calcification potential

Abstract: The use of glutaraldehyde-treated biological tissue in heart valve substitutes is an important option in the treatment of heart valve disease. These devices have limited durability, in part, because of tissue calcification and subsequent tearing of the valve leaflets. Components thought to induce calcification include lipids, cell remnants, and residual glutaraldehyde. We hypothesized that treatment of glutaraldehyde-treated bioprosthetic heart valve material using a short and long chain alcohol (LCA) combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…Inhibition of calcification was noted for ethanol treatment at concentrations of !50%. Treatment of GA-fixed bovine pericardium or porcine aortic valve with mixture of 40% ethanol and 5% 1,2-octanediol solution resulted in reduction of tissue phospholipid content and inhibition of calcification in rat subcutaneous model [7]. It was hypothesized that the removal of phospholipids using a combination of these shortand long-chain alcohols might reduce the calcification, given that long-chain alcohols are more structurally similar to phospholipids than short-chain alcohols and therefore might remove phospholipids more efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of calcification was noted for ethanol treatment at concentrations of !50%. Treatment of GA-fixed bovine pericardium or porcine aortic valve with mixture of 40% ethanol and 5% 1,2-octanediol solution resulted in reduction of tissue phospholipid content and inhibition of calcification in rat subcutaneous model [7]. It was hypothesized that the removal of phospholipids using a combination of these shortand long-chain alcohols might reduce the calcification, given that long-chain alcohols are more structurally similar to phospholipids than short-chain alcohols and therefore might remove phospholipids more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, various methods to remove tissue phospholipids or free aldehyde groups and to reduce the antigenicity of bioprosthetic tissue have been investigated to prevent the calcification of bioprostheses. Ethanol or other alcohol solutions were used to extract tissue phospholipids [6,7], and various amino acids or other amino compounds were used to remove the free aldehyde groups of GA [8][9][10][11][12][13][14][15][16]. Modifications of fixation method using high-concentration GA proved to be effective in the prevention of calcification, presumably by suppressing residual antigenicity of bioprosthetic tissue [8,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Early results are promising but require further investigation on larger studies. Alcohol solutions, including ethanol, have been investigated as a treatment to remove tissue phospholipids, thus preventing calcification (Pathak et al, 2004;Vyavahare et al, 1998). Besides, other techniques have been proposed to minimize the side effects of glutaraldehyde residues on GA-treated pericardium.…”
Section: Pericardium Anti-calcification Treatmentsmentioning
confidence: 99%
“…20 It is noticeable that in a previous study, Pathak et al [25] demonstrated that treatment with 5% ON in 40% ethanol solution sharply reduce phospholipids content in unimplanted BP tissue compared to fresh and GA-fixed BP tissue (0.21 AE 0.05 mg/mg vs 6.7 AE 3.0 mg/mg vs 3.9 AE 0.48 mg/ mg). In contrast, at the same ethanol concentration (40%) without ON, the investigation of Vyavahare et al [10] showed only a negligible decrease of phospholipids content in ethanol treated, unimplanted porcine tissue when compared to GAfixed porcine tissue (16.5 AE 1.5 nmol/mg dry weight vs 17.2 AE 0.8 nmol/mg dry weight).…”
Section: Discussionmentioning
confidence: 91%